Exploring The Implementation of Infographic-Based ‘Gallery Walk’ Technique in EFL Speaking Classroom: A Case Study at One of High School in Karawang - Jasmine, Faeliza; Kusrin; Samsi, Yogi Setia (PROJECT (Professional Journal of English Education), 2025)
This study investigates the implementation of infographic-based Gallery Walk and students’ responses to its implementation. Qualitatively, a case study was employed in this study which the data was taken from observation checklists and semi-structured interviews. Findings indicate that the integration of infographics with a peer-discussion format promotes cognitive, behavioral, and emotional engagement. Students demonstrated improved confidence, critical thinking, and motivation during speaking activities. Infographics served as visual scaffolds that supported idea organization and delivery, while the interactive setting encouraged participation in a low-pressure environment. Despite minor challenges related to pronunciation and time constraints, students responded positively to the activity. Overall, the study concludes that this technique contributes to empowering students’ speaking confidence, engagement, and critical thinking by fostering a collaborative and student-centered learning environment. The study suggests that visual tools combined with collaborative techniques can foster more dynamic and student-centered speaking instruction in secondary education contexts.